The Budget Constrained Multi-Product Newsboy Problem with Reactive Production: A Problem from Entrepreneurial Network Construction (Communications in Mathematical Research, 2021)
This paper develops an extended newsboy model and presents a formulation for this model. This new model has solved the budget contained multi-productnewsboy problem with the reactive production. This model can be used to describethe status of entrepreneurial network construction. We use the Lagrange multiplierprocedure to deal with our problem, but it is too complicated to get the exact solution. So we introduce the homotopy method to deal with it. We give the flow chartto describe how to get the solution via the homotopy method. We also illustrate ourmodel in both the classical procedure and the homotopy method. Comparing the twomethods, we can see that the homotopy method is more exact and efficient.